The Influence Of Animated Video Media On The Development Of Spatial Visual Intelligence In Children Aged 4-5 Years At Al Hidayah Bakung Kindergarten, Blitar Regency In 2023 - Putri Wahyu Wigati; Galuh Pradian Yanuar; Akhmad (Journal of Global Research in Public Health, 2023)
Spatial visual intelligence is intelligence related to visual (vision) and the use of space and making models or images based on the results of observations made before. According to a survey found by researchers in March, 13 children had delayed spatial visual intelligence and 11 were able to recognize images but still needed stimulation. This study aims to determine the influence of animated video media on the development of spatial visual intelligence in children aged 4-5 years at Al Hidayah Bakung Kindergarten, Blitar Regency in 2023. This research uses a pre-experimental design of one group pre test post test design technique carried out at Al Hidayah Bakung Kindergarten, Blitar Regency. The study population of all students aged 4-5 years was 24 respondents. With the technique of sampling the total population. The independent variable of the study was animation media, while the dependent variable of spatial visual intelligence development was measured by the Stanford Binet test. The data were then analyzed by testing Wilcoxon’s hypothesis with α = 0.05.The results of the development of spatial visual intelligence before the provision of animation media from 24 respondents, most of the 13 respondents in the category of children need to get more intensive stimulation and after being given animation media almost all of them, namely 22 respondents are categorized as intelligent children and can develop quite well. The results of the Wilcoxon test show ρ value = 0.000 ≤ α = 0.05 so that H1 is accepted. In conclusion, there is an influence on the development of spatial visual intelligence in children aged 4-5 years. So mothers are expected to be able to maximize the use of animation media as a facility to develop spatial visual intelligence in children aged 4-5 years. Animation media can be given every day for 15 – 20 minutes.